Was facial width-to-height ratio subject to sexual selection pressures? A life course approach - Hodges-Simeon, Carolyn R.; Albert, Graham; Richardson, George B.; McHale, Timothy S.; Weinberg, Seth M.; Gurven, Michael; Gaulin, Steven J. C. (PloS one, 2021)
Sexual selection researchers have traditionally focused on adult sex differences; however, the schedule and pattern of sex-specific ontogeny can provide insights unobtainable from an exclusive focus on adults. Recently, it has been debated whether facial width-to-height ratio (fWHR; bi-zygomatic breadth divided by midface height) is a human secondary sexual characteristic (SSC). Here, we review current evidence, then address this debate using ontogenetic evidence, which has been under-explored in fWHR research. Facial measurements were collected from 3D surface images of males and females aged 3 to 40 (Study 1; US European-descent, n = 2449), and from 2D photographs of males and females aged 7 to 21 (Study 2; Bolivian Tsimane, n = 179), which were used to calculate three fWHR variants (which we call fWHR nasion , fWHR stomion , and fWHR brow ) and two other common facial masculinity ratios (facial width-to-lower-face-height ratio, fWHR lower , and cheekbone prominence). We test whether the observed pattern of facial development exhibits patterns indicative of SSCs, i.e., differential adolescent growth in either male or female facial morphology leading to an adult sex difference. Results showed that only fWHR lower exhibited both adult sex differences as well as the classic pattern of ontogeny for SSCs—greater lower-face growth in male adolescents relative to females. fWHR brow was significantly wider among both pre- and post-pubertal males in the Bolivian Tsimane sample; post-hoc analyses revealed that the effect was driven by large sex differences in brow height, with females having higher placed brows than males across ages. In both samples, all fWHR measures were inversely associated with age; that is, human facial growth is characterized by greater relative elongation in the mid-face and lower face relative to facial width. This trend continues even into middle adulthood. BMI was also a positive predictor of most of the ratios across ages, with greater BMI associated with wider faces. Researchers collecting data on fWHR should target fWHR lower and fWHR brow and should control for both age and BMI. Researchers should also compare ratio approaches with multivariate techniques, such as geometric morphometrics, to examine whether the latter have greater utility for understanding the evolution of facial sexual dimorphism.